In vitro contraceptive activities, molecular docking, molecular dynamics, MM-PBSA, non-covalent interaction and DFT studies of bioactive compounds from Aegle marmelos. Linn., leaves - Gunasekaran, Prasanth; Velmurugan, Yogaswaran; Arputharaj, David Stephen; Savaridasson, Jose Kavitha; Hemamalini, Madhukar; Venkatachalam, Rajakannan (Frontiers in Chemistry, 2023)
Bioactive molecules from natural sources having contraceptive properties were excellent alternatives for modern hormonal contraceptives. Researchers around the world were working on identifying contraceptive leads targeting the male reproductive system rather than the usual female contraceptives. The lack of proper understanding of male contraceptive protein drug targets leads to insufficient evidence on identified contraceptive lead compounds. The proteins specific to the male reproductive system and involved in sperm-egg fusion will be an excellent drug target to identify the male non-hormonal, reversible contraceptive leads. Human sperm hyaluronidases are sperm and seminal fluid-specific enzymes not expressed in somatic cells. and important for sperm-ovum fusion. Inhibiting sperm hyaluronidase activity by natural non-hormonal compounds will lead to reversible and non-hormonal male contraception. The Aegle marmelos Linn. is one such important medicinal plant with valuable phytocompounds used traditionally as a potential contraceptive measure. The in vivo experiments on leaf extracts of Aegle marmelos. Linn containing terpenes, sterols, and alkaloids shows prominent contraceptive activities. Moreover, this study explores the potential ability of the leaf extract on inhibiting the sperm hyaluronidase action with additional molecular details on the interaction between sperm hyaluronidases and three phytocompounds such as aegeline, marmin, and marminol. The in vitro hyaluronidase inhibition assay and Computer Assisted Sperm Analysis (CASA) were used to evaluate the male contraceptive properties of the Aegle marmelos Linn. leaf extract. To identify the interaction profile of aegeline, marmin, and marmenol on sperm cell hyaluronidases the in-silico methods such as molecular docking, Non-Covalent Interaction analysis, Molecular dynamics, and Molecular Mechanics Poisson Boltzmann Surface Area were used. The results of in vitro hyaluronidase inhibition assay and Computer Assisted Sperm Analysis shows the inhibition of hyaluronidase enzymatic activity and reduced sperm activities in the presence of leaf extracts. After incubation with leaf extracts for about 30 minutes time intervals show, the motility drops from progressive to non-progressive and ended up with complete immotile in 100 μg/ml concentration of leaf extract. The results of molecular docking, Non-Covalent Interaction analysis, Molecular dynamics, and Molecular mechanics Poisson Boltzmann Surface Area show that the phytocompounds marmin, and aegeline have the potential ability to inhibit sperm hyaluronidase.